The 1,000th Transplant for Multiple Sclerosis and Other Autoimmune Disorders at the HSCT-México Program: A Myriad of Experiences and Knowledge - Murrieta-Álvarez, Iván; Cantero-Fortiz, Yahveth; León-Peña, Andrés A.; Olivares-Gazca, Juan C.; Priesca-Marín, José Manuel; Ruiz-Delgado, Guillermo J.; Gómez-De-León, Andrés; Gonzalez-Lopez, Elías Eugenio; Jaime-Pérez, José Carlos; Gómez-Almaguer, David; Ruiz-Argüelles, Guillermo J. (Frontiers in Neurology, 2021)
After gaining experience conducting both auto and allografts in persons with hematological diseases in the HSCT programs in Puebla and Monterrey, México, we engaged in autografting patients with autoimmune conditions. The first transplant in multiple sclerosis was conducted in Puebla on July 5, 2006. However, it was until 2015 when we decided to increase our activity autografting persons with autoimmune conditions in the two campuses of the HSCT-México program: Puebla and Monterrey. By December 6th, 2020, we had autografted patient number 1000 in our program. In our experience, a significant reduction in the expanded disability status scale score was achieved in all the three phenotypes of the disease (from a median of 5.1 to 4.5 points), whereas the response rate (defined as decrease of at least 0.5 of EDSS score regardless of baseline EDSS, or unchanged EDSS) was 83, 78 and 73% after 12 months in the relapsing-remitting, primary-progressive and secondary-progressive forms of multiple sclerosis, respectively. In addition to analyzing the viability, safety and efficacy of our method, we have been able to contribute new knowledge in the field of both stem cell transplantation and multiple sclerosis.